Development and application of expertise in elite-level coaches - Walsh, J. (2004)
Research providing insight into how coaches behave has mainly been sourced from an athlete perspective or from observing and recording coach behaviour in context. Only a few studies have recognized the views of the expert coach as a potentially valuable source of information. Yet only coaches can provide insight into their histories, learning, goals, beliefs, knowledge, and decision making, and decode the complex interactions that occur in the dynamic context of coaching. The purpose of this thesis was to investigate how elite-level coaches developed and used expertise. Twenty successful coaches working with Australian junior, elite sport participants were purposefully sampled to cover a diversity of sports (team and individual) and to provide a gender balance.